2018
DOI: 10.3389/fphys.2018.01286
|View full text |Cite
|
Sign up to set email alerts
|

Energy Expenditure as a Function of Activity Level After Spinal Cord Injury: The Need for Tetraplegia-Specific Energy Balance Guidelines

Abstract: The World Health Organization recognizes obesity as a global and increasing problem for the general population. Because of their reduced physical functioning, people with spinal cord injury (SCI) face additional challenges for maintaining an appropriate whole body energy balance, and the majority with SCI are overweight or obese. SCI also reduces exercise capacity, particularly in those with higher-level injury (tetraplegia). Tetraplegia-specific caloric energy expenditure (EE) data is scarce. Therefore, we me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 53 publications
(86 reference statements)
1
9
0
Order By: Relevance
“…Although the cardiovascular outcome was excellent in this patient, rare and significant neurological morbidity has occurred. The researchers reported that patients with tetraplegia after spinal ischemia might have a loss of balance and loss of strength in the lower limb muscles (14). These results supports our study.…”
Section: Discussionsupporting
confidence: 92%
“…Although the cardiovascular outcome was excellent in this patient, rare and significant neurological morbidity has occurred. The researchers reported that patients with tetraplegia after spinal ischemia might have a loss of balance and loss of strength in the lower limb muscles (14). These results supports our study.…”
Section: Discussionsupporting
confidence: 92%
“…Furthermore, it has been reported that individuals with motor-complete tetraplegia utilize ∼50% less VO 2 during exercise than individuals with motor-complete paraplegia ( Holmlund et al, 2018 ). Consequently, Shea and colleagues ( Shea et al, 2018 ) suggested that individuals with higher level injuries may require a greater exercise volume (>220 min per week) to overcome the unique low energy expenditure achieved in this population and observe a health benefit from upper-body exercise. Thus, future research is required to determine optimal ACE prescriptions to effectively and consistently modify body composition and CVD risk factors for adults with chronic SCI.…”
Section: Discussionmentioning
confidence: 99%
“…It is not surprising that healthcare providers commonly mentioned physical limitations and altered body composition as barriers to weight management, particularly as these have been previously identified as barriers to exercise in SCI [ 10 , 11 ]. Following SCI, individuals experience changes in their level of function based on the level of injury, and as a result, reductions in muscle mass [ 17 ] and decreased resting energy expenditure [ 18 ]. Participants also highlighted that as a result of the injury and subsequent bodily changes, these individuals have fewer opportunities to participate in leisure physical activities or exercise and more challenges in shopping and preparing meals.…”
Section: Discussionmentioning
confidence: 99%